AIM portraits: tracing the evolution of artificial intelligence in medicine and predicting its future in the new millennium - Lavrač, Nada; Keravnou-Papailiou, Elpida (My University, 2001)
The purpose behind this special issue of the journal is to report on the scientific experiences of a number of AIM pioneers and to hear their views as to where the field is moving or should move. Unfortunately, not everyone who was invited to contribute his or her portrait, so to speak, and to share with the rest of the community his or her vision for the future, was able to accept the invitation, among them a number of American AIM pioneers. Hence, the overall picture revealed may be a bit biased towards the European AIM endeavors, since out of the seven portraits presented only one comes from a non European researcher. In addition, some of the narrators chose to emphasize their vision for the future, rather than to dwell on the past, assuming perhaps that the lessons from the past or more generally the evolution of the field is reasonably well known to the readership of this journal. Others chose to take us first through the past before analyzing the future. In actual fact no specific instructions were given to the authors. We thought it would be more appropriate to give them the freedom to approach the matter of how to paint their portraits (past, present and envisioned future) in the way they considered most appropriate. At the end of the day we are fortunate to have seven quite different in form, but equally interesting portraits. By and large the seven pioneers come from different countries and different areas of AIM, something that gives added value to their collective accounts. Below we introduce briefly their portraits, in particular their visions for the future
Keywords: Artificial intelligence; Computer science; Medicine; Scientific literature